RECONSTRUCTING THE COMPLEX EVOLUTIONARY ORIGIN OF WILD ALLOPOLYPLOID TOBACCOS (NICOTIANA SECTION SUAVEOLENTES). (27th August 2012) - Kelly, Laura J.; Leitch, Andrew R.; Clarkson, James J.; Knapp, Sandra; Chase, Mark W.
<x xml:space="preserve">Abstract</x> Nicotiana (Solanaceae) provides an ideal system for understanding polyploidization, a pervasive and powerful evolutionary force in plants, as this genus contains several groups of allotetraploids that formed at different times from different diploid progenitors. However, the parental lineages of the largest group of allotetraploids, Nicotiana section Suaveolentes, have been problematic to identify. Using data from four regions of three low‐copy nuclear genes, nuclear ribosomal DNA, and regions of the plastid genome, we have reconstructed the evolutionary origin of sect. Suaveolentes and identified the most likely diploid progenitors by using a combination of gene trees and network approaches to uncover the most strongly supported evidence of species relationships. Our analyses best support a scenario where a member of the sect. Sylvestres lineage acted as the paternal progenitor and a member of either sect. Petunioides or sect. Noctiflorae that also contained introgressed DNA from the other, or a hypothetical hybrid species between these two sections, was the maternal progenitor. Nicotiana exemplifies many of the factors that can complicate the reconstruction of polyploid evolutionary history and highlights how reticulate evolution at the diploid level can add even greater complexity to allopolyploid genomes.